Zooming In and Out: Exploring Teacher Competencies in Inclusive Early Childhood Classrooms. Issue 1 (2nd January 2016) - Lee, Yoon-Joo; Recchia, Susan L.
ABSTRACT: This study explored issues of social inclusion for young children with disabilities through a systematic reanalysis of six preschool case studies focusing on strategies that teachers used in daily practice. Our analysis process entailed a reexamination of classroom observations and teacher inquiry data, focusing back and forth between the "micro" issues of everyday practice and the "macro" issues of inclusion as social justice. Through this process, the authors articulated a set of six overarching teacher competencies and their connection to "big ideas" about inclusion. The findings speak to a growing need within educational settings to move beyond narrow conceptions of ability and disability to take a transformative stance that supports diversity and community for all learners.